POTENTIAL OF THERMOPHIC BACTERIAL XILANASE AS ENVIRONMENTALLY FRIENDLY FABRIC BLEACH - Nur Shofiatun Nisa; IRDAWATI IRDAWATI; Dwi Hilda Putri; Dezi Handayani; Y Yusrizal (Jurnal Serambi Biologi, 2022)
The main conclusion contains what is the implication to other studies or to the future brought by the study. Xylanase is an enzyme that is widely used in industry because this enzyme can hydrolyze xylan (hemicellulose) into xylo-oligosaccharides and xylose. This enzyme can be produced by thermophilic bacteria. One of the benefits of xylanase is as an environmentally friendly fabric bleaching process (biobleaching). The use of xylanase enzymes can reduce the use of toxic chemicals such as chlorine by about 20-40%. The purpose of this study was to determine the effect of temperature and pH on xylanase production activity using rice straw xylan extract as a substrate and to see the potential of MS 18 thermophilic bacterial xylanase on fabric brightness. This research is a descriptive study with temperature and pH optimization treatment using 6 treatments and 3 replications, respectively. Enzyme activity was measured using a spectrophotometer with a wavelength of 540 nm. The data obtained are displayed in the form of tables and figures. The xylanase potential on the brightness level of the fabric was seen based on the results of the kappa number. The results of this study obtained the optimum temperature of xylanase activity at a temperature of 50℃ with the highest xylanase 3.792 U/mL. while at pH the optimum pH of xylanase activity was found at pH 7 with the highest xylanase production of 4.448 U/mL. The potential of xylanase on the brightness of the fabric based on the results of the kappa number is 2.04 lower than without using xylanase, which is 6.46.